Comparative leaching characteristics of fly/bottom ashes from municipal solid waste incineration under various environmental stresses - Yin, Ke (2021)
With proper leaching tests, health hazards associated with municipal solid waste incineration (MSWI) ashes, i.e., incineration bottom ashes (IBA) and incineration fly ashes (IFA), can be quantitatively defined. However, it must be coupled with specific environmental scenarios to draw the proper conclusions. Several environmental stresses based on current management of MSWI ashes were herein simulated with laboratory leaching studies to understand their impacts. The impact of bulk metal recovery on the IBA leaching potential was firstly investigated, suggesting the promoted release for certain metals including those with a relative high content (> 1000 mg/kg) such as Ba, Cu, Pb and Zn. The impact of seawater was also simulated. Most metal release was altered with the new chemistry established. Batch leaching tests were further performed under both salty and acidic environment to understand their aggregated effects, indicating an overwhelming influence from seawater buffering. Lastly, batch leaching tests of the IBA/IFA mixture were performed under various mass ratios, while data were compared with those by their individuals and the theoretical leaching value, unveiling different leaching characteristics during landfill disposal. Hereby, a comprehensive characteristic metal leaching potential was achieved under various ash managements. It provides insights into environmental risks relevant to their current practices.